Prepared to preach God's work and ours in proclaiming His word - Scharf, Greg (Fearn, Scotland Mentor, 2005)
Contents: Preparing to preach; Preparing yourself to preach; Preparing your mind, your body, and the congregation; Preparing the message God gives you to preach. Includes bibliographical references.
Keywords: Preaching